2009
DOI: 10.1093/eurheartj/ehp240
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in intracellular Ca2+ regulation contribute to the pathomechanism of Tako-Tsubo cardiomyopathy

Abstract: In TTC, ventricular expression of SLN and dephosphorylation of PLN potentially result in a reduced SERCA2a activity and its Ca(2+) affinity. Thus, the TTC is associated with specific alteration of Ca(2+)-handling proteins, which might be crucial for contractile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 30 publications
3
83
0
2
Order By: Relevance
“…Even though tako-tsubo was first described in the 1990s, no English language studies appeared before 2000 [4]. The two cases we present suggest that recurrence of tako-tsubo is more frequent than previously thought [2,3,[5][6][7][8][9][10][11][12]. Acute manifestation imitating acute myocardial infarction may be a part of the clinical course of the disease, which is characterized by long periods of remission and sudden onsets with doubtful prognosis of recovery [14].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though tako-tsubo was first described in the 1990s, no English language studies appeared before 2000 [4]. The two cases we present suggest that recurrence of tako-tsubo is more frequent than previously thought [2,3,[5][6][7][8][9][10][11][12]. Acute manifestation imitating acute myocardial infarction may be a part of the clinical course of the disease, which is characterized by long periods of remission and sudden onsets with doubtful prognosis of recovery [14].…”
Section: Discussionmentioning
confidence: 88%
“…Takotsubo cardiomyopathy is also known as apical ballooning syndrome (ABS). It is believed to be triggered by catecholamine stimulation of B1 and B2 receptors which causes decreased expression of regulator proteins SERCa2a and PLN depending on Ca2+ [9]. Most frequently, myocardial stunning affects the apical segments of the heart which is caused by higher affinity to adrenaline.…”
Section: Introductionmentioning
confidence: 99%
“…41 Cardioprotective AKT-1 activation is associated with physiological hypertrophy, whereas a reduction in the AKT/ mTOR pathway is associated with pathological hypertrophy. 42 Interestingly, it has been reported that β2AR-Gi signaling can modulate the cellular PI3K/AKT pathways, indicating a mechanistic link between catecholamine stress and metabolic defects in TTS.…”
Section: -72 Hoursmentioning
confidence: 99%
“…A rapidly accumulating body of evidence has led to very interesting insights into the possible pathophysiology of TTC. Most current hypotheses are based on cathecholamine surges in the setting of acute emotional or physical stress leading to catecholamine-related cardiac toxic effects (32,(44)(45)(46)(47)(48)(49) and was first suggested by Wittstein and colleagues (16). In this section we examine various advancements in understanding TTC pathophysiology.…”
Section: Pathogenesismentioning
confidence: 99%